Regulation of Human γδ T Cells by BTN3A1 Protein Stability and ATP-Binding Cassette Transporters - Rhodes, David A.; Chen, Hung-Chang; Williamson, James C.; Hill, Alfred; Yuan, Jack; Smith, Sam; Rhodes, Harriet; Trowsdale, John; Lehner, Paul J.; Herrmann, Thomas; Eberl, Matthias (Frontiers in Immunology, 2018)
Activation of human Vγ9/Vδ2 T cells by ‘phosphoantigens’ (pAg), the microbial metabolite (E)-4-hydroxy-3-methyl-but-2-enyl pyrophosphate (HMB-PP) and the endogenous isoprenoid intermediate isopentenyl pyrophosphate (IPP), requires expression of butyrophilin BTN3A molecules by presenting cells. However, the precise mechanism of activation of Vγ9/Vδ2 T cells by BTN3A molecules remains elusive. It is not clear what conformation of the three BTN3A isoforms transmits activation signals nor how externally delivered pAg accesses the cytosolic B30.2 domain of BTN3A1. To approach this problem we studied two HLA haplo-identical HeLa cell lines, termed HeLa-L and HeLa-M, which showed marked differences in pAg-dependent stimulation of Vγ9/Vδ2 T cells. Levels of IFN-γ secretion by Vγ9/Vδ2 T cells were profoundly increased by pAg loading, or by binding of the pan-BTN3A specific agonist antibody CD277 20.1, in HeLa-M compared to HeLa-L cells. IL-2 production from a murine hybridoma T cell line expressing human Vγ9/Vδ2 TCR transgenes confirmed that the differential responsiveness to HeLa-L and HeLa-M was TCR dependent. By tissue typing, both HeLa lines were shown to be genetically identical and full-length transcripts of the three BTN3A isoforms were detected in equal abundance with no sequence variation. Expression of BTN3A and interacting molecules such as periplakin or RhoB did not account for the functional variation between HeLa-L and HeLa-M cells. Instead, the data implicate a checkpoint controlling BTN3A1 stability and protein trafficking, acting at an early time point in its maturation. In addition, plasma membrane profiling was used to identify proteins upregulated in HMB-PP treated HeLa-M. ABCG2, a member of the ABC transporter family was the most significant candidate, which crucially showed reduced expression in HeLa-L. Expression of a subset of ABC transporters, including ABCA1 and ABCG1, correlated with efficiency of T cell activation by cytokine secretion, although direct evidence of a functional role was not obtained by knockdown experiments. Our findings indicate a link between members of the ABC protein superfamily and the BTN3A-dependent activation of γδ T cells by endogenous and exogenous pAg.